Новые памятники III-IV вв. н.э. в Юго-Западном Крыму - Пуздровский, А.Е.; Зайцев, Ю.П.; Неневоля, И.И. (Материалы по археологии, истории и этнографии Таврии, 2001)
В 1994-1996 гг. Апьминская экспедиция Крымского филиала ИА НАНУ и Бахчисарайского государственного историко-культурного заповедника провела охранные работы на могильниках позднеантичного времени в среднем и нижнем течении р. Кача у сс. Красная Заря, Тенистое, Суворове Бахчисарайского р-на и у с. Вишневое Севастопольского горсовета. In 1994-1996 Alma expedition of the Crimean Branch of Archaeology Institute of the National Academy of Sciences of Ukraine and Bakhchisarai State History and Culture Reserve undertook rescue works on the cemeteries of the 3rd - 4th centuries AD in the low reaches of the Kacha River near the villages of Krasnaya Zarya, Tenistoe, Suvorovo, Vishnevoe. The monuments were on the territory of the cemeteries or near the Late-Scythian sites of the 1st - 3rd centuries AD. The military threat in the Central and the South-Eastern Crimea in the first quarter - the first third of the 3rd century AD was caused, most likely, by the Alanic invasion and caused the temporal reduction of the Roman presence in Taurica. Beginning with the second quarter of the 4th century AD the number of burials in ditch vaults with plenty of ancient import and weapons. The majority of Chernyakhov type finds are dated back to the same period. The Scythian-Sarmatian population was incorporated into the Goth- Alanic alliance The population of Kacha valley served on the boundaries in the 4th century, defending Chersonesos from possible invasions from the steppe.